Counterspeech: Multidisciplinary Perspectives on Countering Dangerous Speech (Taylor & Francis, 2023)
This volume looks at the forms and functions of counterspeech as well as what determines its effectiveness and success from multidisciplinary perspectives. Counterspeech is in line with international human rights and freedom of speech, and it can be a much more powerful tool against dangerous and toxic speech than blocking and censorship. In the face of online hate speech and disinformation, counterspeech is a tremendously important and timely topic. The book uniquely brings together expertise from a variety of disciplines. It explores linguistic, ethical and legal aspects of counterspeech, looks at the functions and effectiveness of counterspeech from anthropological, practical and sociological perspectives and addresses the question of how we can use modern technological advances to make counterspeech a more instantaneous and efficient option to respond to harmful language online. The greatest benefit of counterspeech lies in the ability to reach bystanders and prevent them from becoming perpetrators themselves. This volume is an excellent opportunity to spread the word about counterspeech, its potential, importance, and future endeavors. This anthology is a great resource for scholars and students of linguistics, philosophy of language, media and communication studies, digital humanities, natural language processing, international human rights law, anthropology and sociology, and interdisciplinary research methods. It is also a valuable source of information for practitioners and anyone who wants to speak up against harmful speech. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.